2001
DOI: 10.1046/j.1440-1819.2001.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimated sleep debt and work stress in Japanese white‐collar workers

Abstract: Sleep debt on weekdays in Japanese white-collar workers, estimated using a questionnaire, was associated with age, overtime, and self-rated workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 1 publication
4
31
0
Order By: Relevance
“…The selected studies concerned 9 European samples (26-28, 36, 41, 43, 47, 49, 50, 51), 4 samples from the United States (29,32,42,48), and 13 Japanese samples (30, 31, 33-35, 37-40, 44-46, 52). Twelve studies had mixed-gender samples (26,27,29,32,34,(41)(42)(43)(47)(48)(49)(50)(51), although one was predominantly male (32) and one predominantly female (48). The other 14 studies had allmale samples (28, 30, 31, 33, 35-40, 44-46, 52).…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected studies concerned 9 European samples (26-28, 36, 41, 43, 47, 49, 50, 51), 4 samples from the United States (29,32,42,48), and 13 Japanese samples (30, 31, 33-35, 37-40, 44-46, 52). Twelve studies had mixed-gender samples (26,27,29,32,34,(41)(42)(43)(47)(48)(49)(50)(51), although one was predominantly male (32) and one predominantly female (48). The other 14 studies had allmale samples (28, 30, 31, 33, 35-40, 44-46, 52).…”
Section: Methodological Characteristics and Resultsmentioning
confidence: 99%
“…Seven studies (30,33,34,39,44,45) investigated associations between extended workhours and hours of sleep. All the studies (except for reference 33) found negative associations between sleep hours on weekdays and extended workhours.…”
Section: Health-related Behaviormentioning
confidence: 99%
“…Two possible explanations for this are (1) that people working long hours on weekdays spend holidays attending to personal matters that cannot be taken care of on weekdays and (2) that they became accustomed to a short sleep duration. Kageyama and colleagues reported that the amount of overtime was positively correlated with the amount of time spent sleeping on the nights before holidays 4) ; however, a later report stated that sleep length before holidays was inversely correlated with overtime 7) . This latter result concurs with that of our study.…”
Section: Discussionmentioning
confidence: 98%
“…The results of our study suggest a need to review this claim and are therefore noteworthy. Kageyama and colleagues reported a significant negative association between ≥60 hours overtime per month in the previous 3 months and sleep length on weekdays among Japanese white-collar workers 7) . Almost half of the women in this study worked <7 hours per day, and most appeared to be parttime workers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation